2013
DOI: 10.1039/c3cp52732h
|View full text |Cite
|
Sign up to set email alerts
|

A folding transition underlies the emergence of membrane affinity in amyloid-β

Abstract: Small amyloid-β (Aβ) oligomers have much higher membrane affinity compared to the monomers, but the structural origin of this functional change is not understood. We show that as monomers assemble into small n-mers (n < 10), Aβ acquires a tertiary fold that is consistent with the mature fibrils. This is an early and defining transition for the aggregating peptide, and possibly underpins its altered bioactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 38 publications
(57 reference statements)
0
43
0
Order By: Relevance
“…Previous simulation studies on beta-sheet-rich beta-amyloid p3 dimer (Jang et al, 2013) on mono-unsaturated PC surfaces and beta-amyloid pentamer (Tofoleanu et al, 2015) on all-unsaturated PC surfaces have also reported spontaneous unfolding of beta-sheets, and therefore agree with our results. Previous studies (McLaurin and Chakrabartty, 1997; Wong et al, 2009; Nag et al, 2013) have revealed that the presence of anionic lipid supports and promotes beta-sheet structures on membrane surfaces. However, in our study, the anionic PS lipids in the PC/PS asymmetric bilayer were not in contact with the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Previous simulation studies on beta-sheet-rich beta-amyloid p3 dimer (Jang et al, 2013) on mono-unsaturated PC surfaces and beta-amyloid pentamer (Tofoleanu et al, 2015) on all-unsaturated PC surfaces have also reported spontaneous unfolding of beta-sheets, and therefore agree with our results. Previous studies (McLaurin and Chakrabartty, 1997; Wong et al, 2009; Nag et al, 2013) have revealed that the presence of anionic lipid supports and promotes beta-sheet structures on membrane surfaces. However, in our study, the anionic PS lipids in the PC/PS asymmetric bilayer were not in contact with the protein.…”
Section: Discussionmentioning
confidence: 99%
“…(263,270) Total internal reflection fluorescence microscopy (TIRFM) enables the visualization of individual Aβ species on membranes and the characterization of their oligomeric states, all at biologically relevant nanomolar concentrations. (58b,280,281) …”
Section: Interactions Of Aβ Peptides With Membranesmentioning
confidence: 99%
“…Aggregates were then resuspended in appropriate amount of phosphate buffer, so that all vortexed solutions had similar tyrosine fluorescence (which ensures matching final peptide concentrations). 10 l of ice-cold H 2 O 2 and 6 l of freshly prepared FeSO 4 were added simultaneously to 600 l of these peptide solutions. These solutions were then vortexed for 60 s. Fluorescence spectra were obtained immediately by exciting at 260 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In this process, the unstructured monomers of A␤ get converted into amyloid fibrils composed of hairpin-shaped monomeric units assembled in a parallel ␤ sheet arrangement (3,4). The central part of this hairpin structure consists of a hydrophilic region flanked by hydrophobic ␤-sheet-forming segments at both ends (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%